Penerapan Program Ekstrakurikuler Calistung Dalam Mengatasi Kesulitan Belajar Membaca, Menulis, Dan Berhitung Pada Siswa Kelas I SD Negeri 01 Sidomukti - Dania Ratna Kurniawati; I Made Ratih Rosanawati (STKIP Subang, 2026)
Reading, writing, and arithmetic skills (calistung) are basic competencies that must be mastered by elementary school students as a foundation for literacy and numeracy development. However, some first grade students still experience difficulties in mastering these skills. This study aims to describe the factors causing learning difficulties in reading, writing, and arithmetic, the implementation of the calistung extracurricular program, and the role of the program in assisting students who experience learning difficulties. This research used a qualitative descriptive approach. The subjects of this study consisted of a first-grade teacher, first-grade students, and parents at SD Negeri 01 Sidomukti. Data were collected through observation, interviews, and documentation. Data analysis used the interactive model consisting of data reduction, data presentation, and conclusion drawing. The results show that learning difficulties in reading, writing, and arithmetic are influenced by internal and external factors. The implementation of the calistung extracurricular program provides additional learning opportunities for students through supportive learning activities and learning media that help students practice reading, writing, and arithmetic.